2022
DOI: 10.1080/21655979.2021.2011631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel natural inhibitors targeting AKT Serine/Threonine Kinase 1 (AKT1) by computational study

Abstract: Despite great progress, the current cancer treatments often have obvious toxicity and side effects. and a poor prognosis (some patients). One of the reasons for the poor prognosis is that certain enzymes prevent anticancer drugs from killing tumor cells. AKT1 is involved in regulating PI3K/AKT/mTOR, a tumor-generating pathway. Ipatasertib, a highly selective inhibitor of AKT1, is widely used in the treatment of tumors. In this study, many structural and biochemical methodswere used to find better AKT1(Threonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The TNF-α antibody in iximab has been clinically proven to be effective in IBD patients (42,43). TNF-β triggers the activation of multiple signaling pathways, such as NF-κB and MAPK, which promote in ammatory response, cell survival, and angiogenesis (44). However, there is limited literature regarding the association of TNF-β with CD.…”
Section: Discussionmentioning
confidence: 99%
“…The TNF-α antibody in iximab has been clinically proven to be effective in IBD patients (42,43). TNF-β triggers the activation of multiple signaling pathways, such as NF-κB and MAPK, which promote in ammatory response, cell survival, and angiogenesis (44). However, there is limited literature regarding the association of TNF-β with CD.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the safety of the adducts, the TOPKAT modules of Discovery Studio were selected to calculate the toxicity of the adducts and PhIP in this study. The original citations for data for this TOPKAT model were obtained from the USEPA AQUIRE database . A previous study showed that PhIP has direct-acting mutagenicity and that subchronic exposure to PhIP induces cancer risk; thus, the Ames mutagenicity and the lowest chronic oral observed adverse effect level (oral rat) in the TOPKAT model were chosen as the toxicity index parameters to compare the toxicity of the adducts against that of PhIP.…”
Section: Methodsmentioning
confidence: 99%
“…[5] There are several potential Akt inhibitors currently in phase II and phase III clinical trials including capivasertib, and ipatasertib. [5][6] The RalGEF pathway, on the other hand, has been relatively unexplored. There are no therapeutic agents targeting this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there exists five FDA‐approved drugs that target the PI3K pathway, such as idelalisib and umbrakisib [5] . There are several potential Akt inhibitors currently in phase II and phase III clinical trials including capivasertib, and ipatasertib [5–6] . The RalGEF pathway, on the other hand, has been relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%